2021
DOI: 10.3389/fcell.2021.620476
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Regulatory Functions of LncRNA SNHG11 in Gastric Cancer Cell Proliferation and Migration

Abstract: The aim of this study was to assess the regulatory functions of SNHG11 in gastric cancer (GC) cell proliferation and migration. Dual-luciferase reporter assay and bioinformatics prediction [starBase (http://starbase.sysu.edu.cn/) and TargetScan (http://www.targetscan.org)] indicated that SNHG11 functions as a miR-184 sponge that can directly act on CDC25A. Compared with normal healthy gastric tissue and mucosal epithelial cell GES-1, SNHG11 and CDC25A expressions were dramatically increased in GC samples and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
(39 reference statements)
0
8
1
Order By: Relevance
“…Bioinformatics prediction is a powerful tool for the study of the function of miRNAs ( 20 ). To predict genes that may regulate SPP1, miRanda was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatics prediction is a powerful tool for the study of the function of miRNAs ( 20 ). To predict genes that may regulate SPP1, miRanda was used.…”
Section: Resultsmentioning
confidence: 99%
“…miR-433 regulates the expression of SPP1 mRNA and protein by directly binding to the 3'-UTR of SPP1 mRNA. Bioinformatics prediction is a powerful tool for the study of the function of miRNAs (20). To predict genes that may regulate SPP1, miRanda was used.…”
Section: Expression Of Mir-433 Is Reduced In Patients Who Have a Tibial Fracture In Combination With Craniocerebral Injury In Comparison mentioning
confidence: 99%
“…The expression levels of FLNB-AS1 are positively correlated with the survival probability of breast cancer patients ( Zhang et al, 2020 ). The SNHG11/miR-184/CDC25A ceRNA network is a new biomarker for the diagnosis, treatment and prognosis of gastric cancer ( Zhao et al, 2021 ). A previous study has shown that HCG18 participates in vascular invasion of hepatocellular cancer by regulating immune cells ( Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the small nucleolar RNA host gene (SNHG) family members (e.g. SNHG6, SNHG11 and SNHG12) are newly recognized important lncRNAs that promote tumor progression through the ceRNA mechanism (22)(23)(24). Increased SNHG6 expression was significantly correlated with poor prognosis of both GC and CRC patients (22,25).…”
Section: Lncrna/circrna-mediated Cerna Crosstalks In Gics: Functional...mentioning
confidence: 99%